Influential Factors that Affect Decisions to Purchase Music Platform Subscriptions in Millennial And Gen-Z Communities in Batam City through Trust Mediation - Hasan, Golan; Scorpianti, Ervi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Advances in technology lead to a major transformation in the means of communication between users and companies. Likewise, the music industry is also experiencing technological innovation, where more and more consumers are subscribing to online music streaming services, both paid and free. The purpose of this study was to determine the effect of usefulness, entertainment, interaction, enjoyment and familiarity on purchase intention for music streaming platform subscriptions in millennial and gen-z communities in Batam City through trust mediation. The research method used in this study is a quantitative method with data from 348 respondents collected through questionnaires and processed through the Partial Least Square program. The results of this research indicate that familiarity and interaction have a significant influence on purchase intention through trust mediation.